Student Digital Assistant Using Android Platform - Ghaffaar, Yanti; , Gunawan Ariyanto, Ph.D; , Dedi Ary Prasetya, S.T (2014)
Students need facilities to support their academic activities and efficiently, using an advanced technology that can process information. The precision, accuracy, and speed is something that is needed for students to manage their studies. Therefore, this needs to be balanced with the availability of increasingly innovative technology. Android technology has recorded as the fastest growing operating system in the mobile world. Many mobile users have switched to android recently. Indirectly, almost all students are Smartphone users with android operating system. Therefore, the authors chose Android as the subject of this study. Therefore, students need an alternative media, which is an android application that can be used. The method used in the making of this application is the equipment analysis, data collection application, design building applications, and application testing. This application is created by using a system that supports the application of the Eclipse IDE and Android SDK. Database used is SQlite. It is considered more effective and efficient than be use of the application manually. For example you can save time, materials, compare to the usage of paper. As the results of research, the application can be used can plan their studies in order to pass by the target.